Certolizumab treatment of localized pyoderma gangrenosum in a pregnant patient - Na Wang; Changping Yu; Weiwei Wang; Qing Yang (Taylor & Francis Group, 2023)
AbstractThe purpose of the article Pyoderma gangrenosum (PG) is an ulcerating neutrophilic dermatosis with an incidence of 3-10 patients per million. PG equally affects patients of both sexes and of any age. Of these patients, 50-75% are associated with auto-immune disease. The lower extremities are the most commonly affected body parts. Minor trauma to the skin may result in the development of new lesions. Patients complain of chronic, nonhealing ulcers with associated pain. Treatment starts with systemic or intralesional corticosteroids, however, no official treatment protocol currently exists. Recent success has been found with biologic agents such as TNF-a inhibitor, although the treatment efficacy in these reports is limited. As for the pregnant patient, the drug selection is difficult. In this report, we want to assess the efficiency of certolizumab in the pregnant patient.Results We report a case of a patient with PG, who responded well to certolizumab, 400 mg as a booster dose, followed by 200 mg biweekly for 8 weeks. The lesions gradually resolved and followed up for 5months without side effect. In addition, we reviewed the literature and compared the current treatment efficiency in the treatment of PG.Conclusion Certolizumab may be a promising therapeutic option for patients with severe PG.